Non-respiratory infections – specific considerations in care homes - Ewan, Victoria; Gordon, Adam (Cambridge University Press, 2010)
This review provides an update on current evidence surrounding the epidemiology, treatment and prevention of non-respiratory infections in care homes. It covers urinary tract infection (UTI), methicillin-resistant staphylococcus aureus (MRSA), decubitus ulcers, scabies, tinea infections and viral and bacterial gastroenteritis. The care home sector provides a unique ecological niche for infections, housing frail older people with multiple co-morbidities and frequent contact with healthcare services in a semi-closed environment. This leads to differences in the diagnosis and management of infections – particularly of outbreaks – when compared with community-dwelling counterparts. It is essential that care home staff play a role in the early recognition, isolation and treatment of infections but they are often not trained as healthcare professionals – this presents a challenge to systematised response. Effective interface between care homes, public health and infection control services are essential to the delivery of care, yet it is not clear how most-effectively to structure such links.